(untitled) (Research, Society and Development, 2023)
Goals: To analyze temporal trends in mortality from liver cancer in adults in the southern states of Brazil from 2000 to 2019. Method: An ecological time series study was conducted. All records regarding mortality from liver cancer in the southern states of Brazil in the period between 2000 and 2019 were analyzed. Mortality rates were calculated and standardized by sex, age by sex and state. Simple linear regression was performed to estimate the trend of mortality. The result obtained is statistically significant (p<0.05). Results: A trend of increase in mortality rates from liver cancer in the South region (p<0.001) was identified. The same was observed for both sexes (p<0.01). The male age group between 60 and 79 years old showed the highest average annual increase. There was a trend towards reduction in rates for the female age groups between 60-69 years old and 80 years or older (p<0.05). In the three states, the upward trend continued: Santa Catarina with an average rate of 11.54/100,000 inhabitants, followed by Rio Grande do Sul with an average rate of 15.53/100,000 inhabitants and Paraná with an average rate of 12.53/100,000 inhabitants. Conclusion: The current study demonstrated an upward trend of liver cancer occurrence in the South region of Brazil.